Handbook of Nanomaterials for Manufacturing Applications - Hussain, Chaudhery Mustansar, editor 645655; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2020)
Handbook of Nanomaterials for Manufacturing Applications covers the challenges and obstacles involved in using nanomaterials in manufacturing. In particular, the lack of information, the possibility of adverse impacts on the environment, human health, safety and sustainability and other remaining challenges. This book addresses these challenges for the use of nanomaterials in major manufacturing sectors and suggests how they may be overcome. It was written to summarize, in a one-stop, concise manner, how nanomaterials and nanotechnology are being used to enhance current manufacturing techniques and processes in order to create more sustainable products in a range of industry sectors. This book will be of great use to materials scientists and engineers who are looking to gain a greater understanding on how nanotechnology is being used to improve the products we use in our daily lives.